2014
DOI: 10.1111/ejn.12541
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic nucleus lesion improves cell survival and functional recovery following dopaminergic cell transplantation in parkinsonian rats

Abstract: Subthalamic nucleus (STN) modulation is currently the gold standard in the treatment of Parkinson's disease (PD) cases refractory to medication. Cell transplantation is a tissue-restorative approach and is a promising strategy in the treatment of PD. One of the obstacles to overcome in cell therapy is the poor dopaminergic cell survival. Our experiment investigates the impact of a partial subthalamotomy prior to ventral mesencephalic (VM) embryonic cell transplantation on dopaminergic cell survival and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…This neurodegenerative effect could be prevented by prior lesioning of the STN, suggesting that it was likely mediated by increased STN activity because of loss of GABA‐ergic tone from the GPe . More recently, partial subthalamotomy was shown to improve cell survival following dopaminergic cell transplantation in 6‐OHDA‐lesioned rats, and the neuroprotective effect of subthalamotomy was confirmed in MPTP‐treated monkeys . Admittedly, the results of these experiments are not universally positive, that is, a neuroprotective effect shown, but a large majority of both rodent and monkey studies have shown a neuroprotective effect (Table ), which could not be judged as minor.…”
Section: The Subthalamic Nucleus As a Target To Halt Neurodegeneratiomentioning
confidence: 99%
“…This neurodegenerative effect could be prevented by prior lesioning of the STN, suggesting that it was likely mediated by increased STN activity because of loss of GABA‐ergic tone from the GPe . More recently, partial subthalamotomy was shown to improve cell survival following dopaminergic cell transplantation in 6‐OHDA‐lesioned rats, and the neuroprotective effect of subthalamotomy was confirmed in MPTP‐treated monkeys . Admittedly, the results of these experiments are not universally positive, that is, a neuroprotective effect shown, but a large majority of both rodent and monkey studies have shown a neuroprotective effect (Table ), which could not be judged as minor.…”
Section: The Subthalamic Nucleus As a Target To Halt Neurodegeneratiomentioning
confidence: 99%
“…Forelimb movement asymmetry and exploratory behavior were tested with the cylinder test (Schallert et al 2000 ; Cordeiro et al 2014 ) following MFB lesion (BL) and in the other sessions indicated above. The animals were placed in the center of a 20-cm-diameter clear Plexiglas cylinder, and their exploratory behavior was recorded with a camera for 4 min.…”
Section: Methodsmentioning
confidence: 99%
“…After ED-1-DAB staining, sections were double-stained for Hematoxylin & Eosin (H&E), using a standard protocol. The sections were mounted on super frost plus slides (Langenbrinck, Emmendingen, Germany), dehydrated in ascending alcohol solutions, and cleared in xylene before they were cover slipped with Histofluid (Marienfeld Laborglas, Lauda-Königshofen, Germany) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%